Flight [videorecording (DVD)] - Zemeckis, Robert, 1952-; Washington, Denzel, 1954-; Cheadle, Don; Reilly, Kelly; Goodman, John, 1952-; Greenwood, Bruce, 1956-; Leo, Melissa (Paramount Pictures, 2017)
A seasoned airline pilot miraculously crash lands his plane after a mid-air catastrophe, saving nearly every soul on board. After the crash, Whip is hailed as a hero, but as more is learned, more questions than answers arise as to who or what was really at fault and what really happened on the plane.